Evaluasi Kebijakan Program Keluarga Harapan (PKH) di Kota Bandar Lampung - Mehita Ayu Nurandani; Bambang Utoyo Sutiyoso; Suripto Suripto (Wacana Publik, 2022)
This study is intended to determine the implementation of PKH in Bandar Lampung City and what factors are the obstacles in its implementation. The method used is descriptive qualitative. Based on the results of the study indicate that the criteria for effectiveness and adequacy are quite good. When viewed from the point of view of PKH's goal of reducing the burden of spending on KPM PKH through access to health services, education services, and complimentary assistance, this program is successful. This success can be seen from the fulfillment of KPM PKH obligations as PKH participants and getting complimentary food assistance. The time efficiency of distribution is still experiencing delays, the distribution of KPM PKH targets has not been maximized, responsiveness in overcoming technical problems is slow, and the accuracy of the program in living self-reliance is not optimal. The inhibiting factors for the implementation of PKH are related to the validity of the data and the KPM mindset.